Metal–organic frameworks vs. buffers: case study of UiO-66 stability. Issue 3 (7th December 2020) - Bůžek, Daniel; Adamec, Slavomír; Lang, Kamil; Demel, Jan
Abstract : The combination of zirconium-based MOF UiO-66 with buffered environment leads to UiO-66 decomposition. Abstract : UiO-66 is a zirconium-based metal–organic framework (MOF) that has numerous applications. Our group recently determined that UiO-66 is not as inert in aqueous dispersions as previously reported in the literature. The present work therefore assessed the behaviour of UiO-66 in buffers: 2-amino-2-(hydroxymethyl)-1, 3-propanediol (TRIS), 4-(2-hydroxyethyl)piperazine-1-ethane sulfonic acid (HEPES), N -ethylmorpholine (NEM) and phosphate buffer (PB), all of which are commonly used in many UiO-66 applications. High performance liquid chromatography and inductively coupled plasma mass spectrometry were used to monitor degradation of the MOF at 25 °C. In each buffer, the terephthalate linker was released to some extent. The chemical nature of the buffer media played a decisive role in the stability with a more pronounced leaching effect in the saline forms of these buffers. The HEPES buffer was found to be the most benign, whereas NEM and PB should be avoided at any concentration as they were shown to rapidly degrade the UiO-66 framework. Low concentration TRIS buffers are also recommended, although these offer minimal buffer capacity to adjust pH. Regardless of the buffer used, rapid terephthalate release was observed, indicating that the UiO-66 was attacked immediately after mixing with the buffer. This process was even more pronounced at 37 °C, i.e., at typical temperature in biological and medical applications. In addition, the dissolution of zirconium, observed in some cases, intensified the UiO-66 decomposition process. These results demonstrate that sensitive analytical techniques have to be used to monitor the release of MOF components so as to quantify the stabilities of these materials in liquid environments.